Utilising benefit-risk assessments within clinical trials-a protocol for the BRAINS project - Totton, N; Julious, S; Hughes, D; Cook, J; Biggs, K; Coates, L; Cook, A; Hewitt, C; Day, S (BioMed Central, 2021)
Background Depending on the treatment to be investigated, a clinical trial could be designed to assess objectives of superiority, equivalence or non-inferiority. The design of the study is affected by many different elements including the control treatment, the primary outcome and associated relationships. In some studies, there could be more than one outcome of interest. In these situations, benefit-risk methodologies could be used to assess the outcomes simultaneously and consider the trade-off between the benefits against the risks of a treatment. Benefit-risk is used within the regulatory industry but seldom included within publicly funded clinical trials within the UK. This project aims to gain an expert consensus on how to select the appropriate trial design (e.g. superiority) and when to consider including benefit-risk methods. Methods The project will consist of four work packages: 1. A web-based survey to elicit current experiences and opinions, 2. A rapid literature review to assess any current recommendations, 3. A two-day consensus workshop to gain agreement on the recommendations, and 4. Production of a guidance document. Discussion The aim of the project is to provide a guideline for clinical researchers, grant funding bodies and reviewers for grant bodies for how to select the most appropriate trial design and when it is appropriate to consider using benefit-risk methods. The focus of the guideline will be on publicly funded trials however, the vision is that the work will be applicable across research settings and we will connect with other organisations and committees as appropriate.